2015
DOI: 10.1063/1.4928205
|View full text |Cite
|
Sign up to set email alerts
|

Spin-transfer-torque efficiency enhanced by edge-damage of perpendicular magnetic random access memories

Abstract: We numerically investigate the effect of magnetic and electrical damages at the edge of a perpendicular magnetic random access memory (MRAM) cell on the spin-transfer-torque (STT) efficiency that is defined by the ratio of thermal stability factor to switching current. We find that the switching mode of an edgedamaged cell is different from that of an undamaged cell, which results in a sizable reduction in the switching current. Together with a marginal reduction of the thermal stability factor of an edge-dama… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A significant decrease of Δ was reported in the case of H k -degradation in an edge damage region. [34][35] Especially for the small MTJ less than 30 nm, these edge damage effects must be considered.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…A significant decrease of Δ was reported in the case of H k -degradation in an edge damage region. [34][35] Especially for the small MTJ less than 30 nm, these edge damage effects must be considered.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…Despite the promising intrinsic properties of CoFeB/MgO, patterned nanoscale devices introduce many complexities including finite size and surface effects, strong magnetostatic interactions and complex magnetization dynamics. Previous experimental [12][13][14] and micromagnetic studies [15][16][17] have concluded that the reversal mechanism is likely to be incoherent due to the large lateral size of the devices. However, the nature of the reversal mechanism and in particular the effects of the localised anisotropy induced at the CoFeB/MgO interface and of the temperature are currently unknown.…”
mentioning
confidence: 99%
“…During the fabrication process, other non-idealities such as edge damages 30 , 31 can be present in the MTJs. We introduced variations in interface anisotropy constant, width and length of the free layer of MTJs, to observe the effect of aforementioned non-idealities.…”
Section: Resultsmentioning
confidence: 99%